Intrusion warning and assessment method for site safety enhancement. (April 2016) - Heng, Li; Shuang, Dong; Skitmore, Martin; Qinghua, He; Qin, Yin
Highlights: Providing a new methodology for personal level unsafe behavior identification, assessment and modification. An approach of integrating real-time location tracking technology into behavior based safety method. A new methodology to enable safety performance improvement. An application to intrusion behavior on construction site is provided. Abstract: Intrusion (unauthorized stepping-into/staying-in a hazardous area), as a common type of near-miss, is the prime cause of the majority of incidents on construction sites including fall from heights, and striking against or being struck by moving objects. Accidents often occur because workers take shortcuts moving about the site without fully perceiving the potential dangers. A number of researches have been devoted to developing methods to prevent such behaviors mainly based on the theory of Behavior-Based Safety (BBS), which aims to cultivate safety behaviors among workers in accordance with safety regulations. In current BBS practice, trained observers and safety supervisors are responsible for safety behavior inspections following safety plans and operation regulations. The observation process is time-consuming and its effectiveness depends largely on the observer's safety knowledge and experience, which often results in omissions or bias. This paper presents a reformed safety behavior modification approach by integrating a location-based technology with BBS. Firstly, a detailed background is provided, covering current intrusion problems on site, existing use of BBS for behavior improvement, difficulties in achieving widespread adoption and potential technologies for location tracking and in-time feedback. Then, a conceptual framework of positioning technology-enhanced BBS is developed, followed by details of the corresponding on-line supporting system, Real Time Location System (RTLS) and Virtual Construction System (VCS). The application of the system is then demonstrated and tested in a construction site in Hong Kong. Final comments are made concerning further research direction and prospects for wider adoption.